EXCEPTIONS TO PRINCIPLE OF AUTONOMY IN DOCUMENTARY LETTERS OF CREDIT; A COMPARATIVE VIEW - H. Alavi (Russian Journal of Economics and Law)
Objective: comparative analysis of exceptions to the principle of autonomy of documentary letters of credit.Methods: dialectical method, systemic method, analysis, synthesis, comparison.Results: it is proved that documentary letters of credit are among the most popular methods of payment in international trade which facilitate the process of transaction by replacing risk of payment by applicant buyer with the guarantee of bank. It is proved that operation of documentary letters of credit (LC) is subjected to two globally recognized principles of autonomy (independence) and strict compliance. A rule is identified, according to which courts in different countries started to recognize exceptions to the principle of autonomy in international LC transaction despite their reluctance in interfering in function of autonomy principle. Scientific novelty: the article views the principle of autonomy and recognized exceptions to it in comparative aspect, proves the to recognize exceptions to the principle of autonomy in international LC transaction among common law jurisdictions, lists the exceptions recognized by courts and analyzes the attitude of the courts in other common law jurisdictions. Practical significance: the paper is addressed to researchers and educators, practicing lawyers, graduate and post-graduate students, and everyone interested in the principle of autonomy of documentary letters of credit.